RESOURCE PRODUCTIVITY AND PRICE SPREAD ANALYSIS OF PADDY MARKETING IN ANDHRA PRADESH - R. VIJAYA KUMARI, B. SOWJANYA, D. V. SUBBA RAO and (The Journal of Research, PJTSAU, 2019)
The present study was undertaken in the year 2011-12 in Nalgonda district of Andhra Pradesh to study the resource productivity and price spread analysis of paddy. A sample of 15 farmers and 70 intermediaries were selected. Cobb Douglas production function analysis was employed to know the resource productivity of paddy. The coefficient of multiple determination, R2 indicated that 77 percent of the variation in income was explained by the independent variables included in production function. Production coefficient of area and marketing costs had turned out to be significantly influencing the income of the farmers. Labour costs were negatively significant. Returns to scale was 1.81 which is more than unity indicating increasing returns to scale. Two marketing channels were identified for price spread analysis in the study area. Marketing costs borne by producer, trader, processor, wholesaler and retailer were Rs.117.02, Rs. 40.63, Rs. 96.46, Rs. 96.28 and Rs. 34.18 in channel I. Marketing costs borne by producer, processor, and retailer in channel II were Rs. 115.86, Rs. 118.72 and Rs. 39.60. In channel I retailer secured high margin followed by processor, wholesaler and trader. Producer share in consumer’s rupee was high in channel I (70.66) compared to channel II (58.80). Marketing efficiency in channel II was high compared to channel I.